2011
DOI: 10.1093/icesjms/fsr090
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and quantity of Alaskan groundfish catcher-vessel landings made with and without an observer

Abstract: Faunce, C. H., and Barbeaux, S. J. 2011. The frequency and quantity of Alaskan groundfish catcher-vessel landings made with and without an observer. – ICES Journal of Marine Science, 68: 1757–1763. The North Pacific Groundfish Observer Programme (NPGOP) is one of the largest on-board fishery-monitoring programmes in the world, and the data are used extensively for both in- and post-season management of fisheries. Within certain limits, Alaskan fishers determine when and where to carry observers. There may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…In observer studies, several assumptions are usually required, including one that observed trips were representative of those done by all operators and that the fishing locations, times and practices covered were not influenced by the presence of an observer (Faunce & Barbeaux, ; Liggins, Bradley & Kennelly, ). Although not all operators participated in sampling, observed and non‐observed vessels from each port fished the same times and locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In observer studies, several assumptions are usually required, including one that observed trips were representative of those done by all operators and that the fishing locations, times and practices covered were not influenced by the presence of an observer (Faunce & Barbeaux, ; Liggins, Bradley & Kennelly, ). Although not all operators participated in sampling, observed and non‐observed vessels from each port fished the same times and locations.…”
Section: Discussionmentioning
confidence: 99%
“…ered were not influenced by the presence of an observer(Faunce & Barbeaux, 2011;Liggins, Bradley & Kennelly, 1997). Although not all…”
mentioning
confidence: 80%
“…This monitoring can ensure compliance around MPA boundaries; however, enforcement can often be more complicated than just tracking presence or absence inside closed areas. Enforcing gear compliance can be more challenging and often requires close monitoring of activities, which can be accomplished by an observer program such as the ones used for fi sheries in the U.S (Faunce and Barbeaux, 2011) or increasingly effective electronic monitoring programs.…”
Section: Mpa Monitoringmentioning
confidence: 99%
“…fishing effort and location). Information collected by observers has been used extensively in stock assessments and the provision of management advice (Faunce and Barbeaux ). Observers can provide a strong direct link between fishers and science thereby promoting good communication (Cotter and Pilling ).…”
Section: Merits Of Technologies and Approaches In Documenting Total Cmentioning
confidence: 99%